10th EASN International Conference on Innovation in Aviation & Space to the Satisfaction of the European Citizens - Pantelakis, Spiros; Strohmayer, Andreas; Guadagno, Liberata (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue book contains selected papers from works presented at the 10th EASN (European Aeronautics Science Network) International Conference on Innovation in Aviation & Space, which was held from the 2nd until the 4th of September, 2020. About 350 remote participants contributed to a high-level scientific gathering providing some of the latest research results on the topic, as well as some of the latest relevant technological advancements. Eleven interesting articles, which cover a wide range of topics including characterization, analysis and design, as well as numerical simulation, are contained in this Special Issue.